A stable relationship: isotopes and bioarchaeology are in it for the long haul. (8th August 2017) - Britton, Kate
Abstract : Given their ubiquity in dietary reconstruction, it is fitting that the story of isotopes began with a conversation over dinner. Although coined in scientific literature by Frederick Soddy (1913 ), the word 'isotope' was first conceived by Margaret Todd, a medical doctor (also known as the novelist 'Graham Travers', and an all-round gender-stereotype-smasher of their age). In 1912, Soddy and Todd were attending a supper in Glasgow. When talk turned to work, Soddy described the then nameless concept of elements of different masses that occupy the same place in the periodic table. Todd suggested the term 'isotope', from the Greek isos ('same') + topos ('place'), and the name stuck (Nicol1957 ; Nagel1982 ).